La poesia valenciana de la restauració (1874-1902) - Verger, Eduard J. (Caplletra. Revista Internacional de Filologia, 2015)
More has been written on the politics and ideology of the Renaixença in Valencia than on the aesthetics of its literature. The author analyzes the innovative literary production of a group of poets of the Restoration who have been ignored until now.